Clinical Rating Scales for Urinary Symptoms in Parkinson Disease: Critique and Recommendations. Issue 5 (25th October 2018) - Pavy‐Le Traon, Anne; Cotterill, Nikki; Amarenco, Gerard; Duerr, Susanne; Kaufmann, Horacio; Lahrmann, Heinz; Tison, François; Wenning, Gregor K.; Goetz, Christopher G.; Poewe, Werner; Sampaio, Cristina; Schrag, Anette; et al.
Abstract: Background: The prevalence of lower urinary tract symptoms (LUTS) is high in Parkinson's disease (PD). These problems negatively affect quality of life and include both storage and voiding problems. The International Parkinson and Movement Disorder Society established a task force to review clinical rating scales/questionnaires for the assessment of urinary symptoms in PD. Methods: According to prespecified criteria, these scales/questionnaires were classified as "Recommended" or "Recommended with caveats" when clinimetric properties were satisfactory for Recommended status but had not been assessed specifically in PD, "Suggested" or "Listed." These assessments were applied to rate scales as screening tools for the diagnosis of LUTS and for the rating of symptom severity. Results: Among scales that included LUTS but focused on overall autonomic or non‐motor symptoms in PD, no scale reached the clinimetric rigor to be designated as Recommended or Recommended with caveats, but some were Suggested for either diagnostic screening tools or severity measures. Among primary urological scales, most are well validated in urological setting, but none was validated specifically in PD. DAN‐PSS (Danish PSS), ICIQ (International Consultation for Incontinence Questionnaire)‐MLUTS (Male Lower Urinary Tract Symptoms), OABq, OABq‐SF (ICIQ‐OABqol), OAB‐V8 (as screening tool), and OABSS (OAB Symptom Score) met criteria for Recommended with caveats. Conclusion: The Task Force does not recommend the development of a new scale. However, all above‐mentioned questionnaires need to be studied further and specifically validated in PD.